Experiencing sweet taste is associated with an increase in prosocial behavior - Michael Schaefer; Anja Kühnel; Felix Schweitzer; Franziska Rumpel; Matti Gärtner (Scientific Reports, 2023)
Abstract Taste may be the first sense that emerged in evolution. Taste is also a very important sense since it signals potential beneficial or dangerous effects of foods. Given this fundamental role of taste in our lives, it is not surprising that taste also affects our psychological perception and thinking. For example, previous research demonstrated remarkable psychological effects of sweet taste experiences, suggesting that sweetness may be a source domain for prosocial functioning. Recent research reports that briefly experiencing sweet taste made participants more helpful in their intentions and behavior. The current study aims to test this hypothesis and to examine the neural underpinnings of this effect by using an fMRI approach. Participants were asked to taste sweet, salty, and neutral taste while lying in the fMRI scanner. Subsequently their prosocial behavior was tested by playing the dictator game, a measure of prosocial behavior. Results showed that sweet taste was associated with an increase in prosocial behavior compared with previously experiencing salty taste but did not affect control stimuli ratings. FMRI results revealed a modulation of the dorsal anterior cingulate cortex associated with this sweetness effect. This brain area is known to play a central role for monitoring conflicts and decisions and has been directly linked to selfish and prosocial economic decisions. The results demonstrate that sweet taste has complex psychological effects including positive and socially desirable outcomes. We discuss the results with other studies on psychological sweetness effects and suggest possible implications of these findings.